2017
DOI: 10.3233/jad-170612
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Music Playlists for People with Dementia: A Critical Synthesis

Abstract: The use of pre-recorded music to ease behavioral and psychological symptoms associated with dementia is popular in health-care contexts in both formal music therapy settings and in non-therapist led interventions. However, further understanding of how non-therapist led interventions compare to therapist led interventions is needed. This paper reviews 28 studies that used pre-recorded music with people with dementia using a critical interpretive synthesis model. Results revealed that pre-recorded music can be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 45 publications
(43 reference statements)
1
71
0
2
Order By: Relevance
“…[24][25][26][27][28][29] Such interventions have also captured the media's interest, evidenced by the creation of a documentary titled Alive Inside which depicts the positive experiences of people with dementia who have been rejuvenated by listening to personalised music. 30 Previous literature reviews on the use of prerecorded music playlists 31 and music as a therapy 32 for PWDs found that positive effects were evident in therapist or non-therapist-led interventions as well as caregiver-implemented interventions. Similarly, results from a meta-analysis suggested the higher likelihood of positive outcomes with music listening compared to music therapy.…”
Section: Rationalementioning
confidence: 99%
“…[24][25][26][27][28][29] Such interventions have also captured the media's interest, evidenced by the creation of a documentary titled Alive Inside which depicts the positive experiences of people with dementia who have been rejuvenated by listening to personalised music. 30 Previous literature reviews on the use of prerecorded music playlists 31 and music as a therapy 32 for PWDs found that positive effects were evident in therapist or non-therapist-led interventions as well as caregiver-implemented interventions. Similarly, results from a meta-analysis suggested the higher likelihood of positive outcomes with music listening compared to music therapy.…”
Section: Rationalementioning
confidence: 99%
“…Studies have shown that non-personalized music might increase anxiety and depression in patients with dementia. 6,25 It was vital to organize active song sessions in groups with staff present all the time. Several strategies related to music therapy are described, and distinction is often made between a receptive approach (listening to music) and an active approach (i.e., participating).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been found in other studies. 6,25 People with dementia are as varied as people without it, and they have their own backgrounds, histories, and preferences. Music is found to be closely associated with each person's identity, history, and earlier life events, which are often linked to a particular type of music.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations